Research Trends in Geographic Information Science - Navratil, Gerhard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
In June/July 2008 the Institute for Geoinformation and Cartography at the Vienna University of Technology organized a scientific colloquium in this city, where 15 well-known scientists presented their ideas on research for the upcoming decade. This book contains papers prepared by the participants as well as by other researchers. The eighteen papers in this book reflect the opinion of a core group of Geoinformation scientists about future research topics. Dealing with these topics poses multiple research questions for the coming years.
Section I: Philosophical background and Semantics -- Ontology, Epistemology, Teleology: Triangulating Geographic Information Science -- Geonoemata Elicited: Concepts, Objects, and Other Uncertain Geographic Things -- Virtue Ethics for GIS Professionals -- Why Is Scale an Effective Descriptor for Data Quality? The Physical and Ontological Rationale for Imprecision and Level of Detail -- Semantic Engineering -- Section II: Mathematical Methods -- A Common Spatial Model for GIS -- Computation with Imprecise Probabilities -- Spatial Data Quality: Problems and Prospects -- Latent Analysis as a Potential Method for Integrating Spatial Data Concepts -- Stereology for Multitemporal Images with an Application to Flooding -- Modeling Spatiotemporal Paths for Single Moving Objects -- Moving Objects in Databases and GIS: State-of-the-Art and Open Problems -- The Degree Distribution of Random Planar Graphs -- Section III: Tools and Applications -- Geographical Information Engineering in the 21 Century -- Towards Visual Summaries of Geographic Databases Based on Chorems -- Intelligent Spatial Communication -- Training Games and GIS -- Cadastre and Economic Development.
Keywords: Geography; Geotechnical engineering; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Geotechnical Engineering & Applied Earth Sciences; Electronic books